Official Marimba guide to Bongo - Goodman, Danny (Sams.net, 1997)
Bongo is the new Java-based graphical interface design and development product from Marimba, Inc. - the hot Silicon Valley startup founded by four original members of the Sun Java team. Just as Marimba's Castanet technology is changing the way Java applications are distributed, Bongo is changing the way Java applications are developed, enabling programmers and application designers of all skill levels to quickly create a user interface to a Java application using a variety of predesigned widgets, images, audio, and animation.